Composition and Biogeography of Planktonic Pro- and Eukaryotic Communities in the Atlantic Ocean: Primer Choice Matters - Milke, Felix; Sanchez-Garcia, Selene; Dlugosch, Leon; McNichol, Jesse; Fuhrman, Jed; Simon, Meinhard; Wagner-Döbler, Irene (Frontiers in Microbiology, 2022)
Basin-scale biogeographic observations of marine pelagic pro- and eukaryotic communities are necessary to understand forces driving community composition and for providing a baseline to monitor global change. Deep sequencing of rRNA genes provides community composition at high resolution; yet, it is unclear how the choice of primers affects biogeographic patterns. Here, we re-amplified 16S rRNA genes from DNA sampled during R/V Polarstern Cruise ANT28-5 over a latitudinal transect across the Atlantic Ocean from 52°S to 47°N using universal V4-V5 primers and compared the results with those obtained previously with V5-V6 bacteria-specific primers. For validation of our results, we inferred community composition based on 16S rRNA genes of metagenomes from the same stations and single amplified genomes (SAGs) from the Global Ocean Reference Genome (GORG) database. We found that the universal V4-V5 primers retrieved SAR11 clades with similar relative proportions as those found in the GORG database while the V5-V6 primers recovered strongly diverging clade abundances. We confirmed an inverse bell-shaped distance-decay relationship and a latitudinal diversity gradient that did not decline linearly with absolute latitude in the Atlantic Ocean. Patterns were modified by sampling depth, sequencing depth, choice of primers, and abundance filtering. Especially richness patterns were not robust to methodological change. This study offers a detailed picture of the Atlantic Ocean microbiome using a universal set of PCR primers that allow for the conjunction of biogeographical patterns among organisms from different domains of life.